APLIKASI CUSTOMER RELATIONSHIP MANAGEMENT DIGITAL PRINTING PADA CV. MATAHARI DIGITAL PRINTING DI SEMARANG (Information Technology and Telematics, 2015)
Abstrak : -- Quite a lot of employmen, and human activities related to computers and aided by computer. Just as in the process of printing of softcopy into hardcopy. So it appears the so-called digital printing business. By utilizing the internet facility, the business is expected to grow rapidly and create a good relationship between the company and the customers are often called CRM. To enhance the company's relationship with the customer in terms of printing documents, CRM Applications of Digital Printing at CV. Matahari Digital Printing in Semarang is expected to help enable customers to print documents more efficiently, and increase the number of customers and customer loyalty. With a web-based, will facilitate information, data, and services up to a short time. Keywords : -- Digital printing, CRM, web programing Abstrak : -- Cukup banyak kegiatan, pekerjaan, dan aktivitas manusia yang berhubungan dengan komputer dan dibantu oleh komputer. Seperti halnya dalam proses pencetakan (printing) dari soft document menjadi hardcopy. Sehingga muncul suatu bisnis yang disebut digital printing. Dengan memanfaatkan fasilitas internet, bisnis ini diharapkan dapat berkembang pesat dan menciptakan hubungan yang baik antara perusahaan dan pelanggan yang sering disebut CRM. Untuk meningkatkan hubungan perusahaan dengan pelanggan dalam hal printing dokumen, Aplikasi CRM Digital Printing Pada CV. Digital Printing di semarang diharapkan dapat membantu memudahkan pelanggan dalam mencetak dokumen, lebih efisien, serta meningkatkan jumlah pelanggan dan loyalitas pelanggan. Dengan berbasis web, akan mempermudah informasi, data, dan layanan sampai dengan waktu yang singkat. Kata Kunci : -- Digital printing, CRM, web programing